Computational reconstitution of spine calcium transients from individual proteins - Bartol, Thomas M.; Keller, Daniel X.; Kinney, Justin P.; Bajaj, Chandrajit L.; Harris, Kristen M.; Sejnowski, Terrence J.; Kennedy, Mary B. (Frontiers in Synaptic Neuroscience, 2015)
We have built a stochastic model in the program MCell that simulates Ca2+ transients in spines from the principal molecular components believed to control Ca2+ entry and exit. Proteins, with their kinetic models, are located within two segments of dendrites containing 88 intact spines, centered in a fully reconstructed 5 x 5 x 6 µm cube of hippocampal neuropil. Protein components include AMPA- and NMDA-type glutamate receptors, L- and R-type voltage-dependent Ca2+ channels, Na+/Ca2+ exchangers, plasma membrane Ca2+ ATPases, smooth endoplasmic reticulum Ca2+ ATPases, immobile Ca2+ buffers, and calbindin. Kinetic models for each protein were taken from published studies of the isolated proteins in vitro. For simulation of electrical stimuli, the time course of voltage changes in the dendritic spine was generated with the desired stimulus in the program NEURON. Voltage-dependent parameters were then continuously re-adjusted during simulations in MCell to reproduce the effects of the stimulus. Nine parameters of the model were optimized within realistic experimental limits by a process that compared results of simulations to published data. We find that simulations in the optimized model reproduce the timing and amplitude of Ca2+ transients measured experimentally in intact neurons. Thus, we demonstrate that the characteristics of individual isolated proteins determined in vitro can accurately reproduce the dynamics of experimentally measured Ca2+ transients in spines. The model will provide a test bed for exploring the roles of additional proteins that regulate Ca2+ influx into spines and for studying the behavior of protein targets in the spine that are regulated by Ca2+ influx.